A regional response to tuberculosis amid COVID-19 in southern Africa : towards eliminating silicosis and ending tuberculosis by 2030 - Khoza, Norman; Chamdimba, Chimwemwe; Moyo, Dingani; Chirime, Ivandra; Ng’andu, Brian Mutale (Mettamedia (Pty) Ltd, 2022)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is one of the oldest known communicable diseases, dating back more than three million years. It has always been associated with high morbidity and mortality rates and is one of the top 10 causes of deaths, and the leading cause of death from a single infectious agent, currently ranked above HIV/AIDS. TB is responsible for 1.5 million deaths globally per year, including 251 000 in people with HIV. Approximately 24% of the global cases of TB in 2018 were from the World Health Organization (WHO) Africa region – ranked second after south-east Asia at 44%. Over the centuries, TB was known by many different names, such as phthisis in Greece, schachepheth in biblical times, the king’s evil in England and France, and white plague in the 18th century. Later, TB was called ‘captain of all these men of death’ because of its epidemic proportions in Europe and North America, being the cause of one in four deaths. Hippocrates described phthisis as a fatal disease, especially for young adults.